The game of eating smart : nourishing recipes for peak performance inspired by MLB superstars - Loria, Julie (Rodale, 2019)
In Major League Baseball, the transition to eating healthy food has become more than a movement; it<U+2019>s a revolution. Jose Altuve, Chris Archer, Clayton Kershaw, Noah Syndergaard, Mike Trout, and the 16 other star ballplayers featured in The Game of Eating Smart are proof of the positive effect of proper nutrition on athletic performance and overall health. Eating smart isn<U+2019>t about calorie-counting and fad diets. It simply means consuming more nourishing food<U+2014>including leafy greens, lean protein, and fresh fruit<U+2014>that eventually decreases the desire to make unhealthy choices. The Game of Eating Smart includes insights from today<U+2019>s top players on their approach to healthy living and performance nutrition, plus more than 80 easy-to-prepare and nutrient-dense recipes inspired by their food philosophies and favorite meals.